2000
DOI: 10.1023/a:1011451710004
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: It is widely accepted that glucagon stimulates GH, ACTH and cortisol release in humans, though the mechanisms underlying these effects are unclear. Aim of the present study was to evaluate the stimulatory effect of intramuscolar (i.m.) and intravenous (i.v.) glucagon (GLU) administration on ACTH, cortisol (F) and GH release in normal adult subjects and to compare its effect on hypothalamo-pituitary adrenal (HPA) axis with that of hCRH. To this goal, in 6 normal young women (26-32 yrs, 50-58 kg) we studied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Josefsberg et al [33] observed a GH response to iv glucagon that was similar to the one observed following iv arginine. In contrast, three studies performed in adults [35, 36] and children [37] observed a poor or absent GH response following iv administration of 1 mg glucagon, contrasting with a good GH response following im or sc administration of 1 mg glucagon despite similar changes in blood glucose. Cortisol response was similarly affected by the route of administration of glucagon, at least in adults [36].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Josefsberg et al [33] observed a GH response to iv glucagon that was similar to the one observed following iv arginine. In contrast, three studies performed in adults [35, 36] and children [37] observed a poor or absent GH response following iv administration of 1 mg glucagon, contrasting with a good GH response following im or sc administration of 1 mg glucagon despite similar changes in blood glucose. Cortisol response was similarly affected by the route of administration of glucagon, at least in adults [36].…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, three studies performed in adults [35, 36] and children [37] observed a poor or absent GH response following iv administration of 1 mg glucagon, contrasting with a good GH response following im or sc administration of 1 mg glucagon despite similar changes in blood glucose. Cortisol response was similarly affected by the route of administration of glucagon, at least in adults [36]. In a recent review, Sizonenko et al [13] suggested that the route of administration could influence the timing of the GH response.…”
Section: Discussionmentioning
confidence: 98%
“…The result is that tumor cells mobilize body stores in anabolic and glycolytic conditions, to build the tumor mass using body stores, the metabolic rewiring linked to the blockade of PK and PDH in tumor cells and in body stores is schematized in Figure 1B, in tumor cells PK and PDH are inactivated via PKA signals, while the other tumor enzymes are boosted via PKB. Moreover, the release of glucagon acts on central neurons releasing corticotropin-releasing hormone (CRH), which increases ACTH release [16]. The latter, triggers the release of glucocorticoids (cortisol) from the adrenal cortex that binds to steroid receptors in muscles inducing proteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the central action of glucagon [16] increases growth hormone release and then IGF, which boosts the insulin effect. Somatostatin release from delta cells cannot attenuate Growth Hormone-IGF actions since the increase of epinephrine, resulting from the lower GABA released, blocks the delta cells [15], epinephrine instead does the job for GABA.…”
Section: Introductionmentioning
confidence: 99%